Processing visual information in elite junior soccer players: Effects of chronological age and training experience on visual perception, attention, and decision making - Klatt, S.; Smeeton, N. J. (European Journal of Sport Science, 2022)
Processing information in peripheral vision is an important perceptual-cognitive skill in team sports. The relative contribution of various perceptual-cognitive skills to expertise in sports throughout adolescence has not been investigated in detail yet. The current study examined the effects of chronological age and training experience on perception, attention, and decision making in young soccer players. Sixty-five elite youth players were required to judge different game situations in a decision-making task involving both perceptual (object detection) and attentional (postural feature recognition) skills to perceive player configurations in the visual periphery. In general, performance decreased in the decision-making and feature-recognition tasks with increasing use of peripheral visual field, but not in the object-detection task. Superior performances were found for under 18 years old players compared to under 16 years old players especially in their attentional skills. Higher training experience affected decision-making and attentional performance. Overall, the findings provide insights and implications for training perceptual-cognitive skills in team sports.